Structural Characterizations and Biological Evaluation of a Natural Polysaccharide from Branches of Camellia oleifera Abel - Shengjia Lu; Yali Zhang; Yanghui Ou; Jianghui Xin; Hongliang Yao; Litao Guan (Pharmaceuticals)
Background: Camellia oleifera Abel (C. oleifera) is widely cultivated and serves as an important source of edible oil. Yet, during oil production, pruned branches generate significant waste and contribute to environmental pollution. Objectives: In this work, we obtain a natural polysaccharide from the branches of C. oleifera and optimize its extraction using Box–Behnken design (BBD), which is a statistical method commonly used in response surface methodology. Additionally, we study its properties, such as monosaccharide composition, structural features, antioxidant, and anti-inflammatory abilities. Results: BBD was employed to optimize polysaccharide extraction (solid-liquid ratio = 1:40; 90 °C; 130 min) for a higher yield. After purification, the major monosaccharides of branches of C. oleifera’s polysaccharide (CBP) were disclosed as glucose and galactose. Subsequent structural features of CBP were measured. The antioxidant and anti-inflammatory abilities were measured. The highly scavenging rates of the 2,2-diphenyl-1-picrylhydrazyl and hydroxyl radicals, with the chelating capacity of Fe2+, indicate potent antioxidant activity of CBP. Conclusions: In general, CBP demonstrated significant anti-inflammatory activity with down-regulating the expression of IL-6 and IL-1β in the LPS-induced macrophage RAW264.7 model. This bioactive polysaccharide adds value to waste branches by offering a novel approach to waste recycling and the development of C. oleifera.